Chemokines: key players in cancer progression and metastasis - Singh, Rajesh (2011)
Instructed cell migration is a fundamental component of various biological systems and is critical to the pathogenesis of many diseases including cancer. Role of chemokines in providing navigational cues to migrating cancer cells bearing specific receptors is well established. However, functional mechanisms of chemokine are not well implicit, which is crucial for designing new therapeutics to control tumor growth and metastasis. Multiple functions and mode of actions have been advocated for chemokines and their receptors in the progression of primary and secondary tumors. In this review, we have discussed current advances in understanding the role of the chemokines and their corresponding receptor in tumor progression and metastasis.